2019
DOI: 10.1007/s11605-018-4062-9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age on Complications and Overall Survival After Ivor Lewis Totally Minimally Invasive Esophagectomy

Abstract: Background The number of elderly patients suffering from esophageal cancer is increasing, due to an increasing incidence of esophageal cancer and increasing life expectancy. However, the effect of age on morbidity, mortality, and survival after Ivor Lewis total minimally invasive esophagectomy (TMIE) is not well known. Methods A prospectively documented database from December 2010 to June 2017 was analyzed, including all patients who underwent Ivor Lewis TMIE for esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
(39 reference statements)
0
21
1
Order By: Relevance
“…However, past studies have noted rates of delirium vary with age after the performance of the same type of esophagectomy (eg, Ivor Lewis). 30 Finally, of note, our study identified different lab values associated with delirium such as elevated WBC and AST/SGOT but we did not find statistical differences in values of BMI or albumin which have been noted after other surgical procedures types to be positively associated with delirium. 27 It is important to note that while elevated WBC and AST and INR are associated with delirium, these makers may represent a subclinical preoperative infection or underlying cirrhosis and potential for hepatic encephalopathy development that was not accounted for.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, past studies have noted rates of delirium vary with age after the performance of the same type of esophagectomy (eg, Ivor Lewis). 30 Finally, of note, our study identified different lab values associated with delirium such as elevated WBC and AST/SGOT but we did not find statistical differences in values of BMI or albumin which have been noted after other surgical procedures types to be positively associated with delirium. 27 It is important to note that while elevated WBC and AST and INR are associated with delirium, these makers may represent a subclinical preoperative infection or underlying cirrhosis and potential for hepatic encephalopathy development that was not accounted for.…”
Section: Discussioncontrasting
confidence: 56%
“…We did not further analyze variables between patients undergoing each procedure. However, past studies have noted rates of delirium vary with age after the performance of the same type of esophagectomy (eg, Ivor Lewis) …”
Section: Discussionmentioning
confidence: 99%
“…However, these three meta-analyses did not include studies on MIE, and excluded studies that used other age thresholds. In contrast, recent individual studies that compared older with younger patients who underwent MIE showed comparable rates of anastomotic leak as well as 30-d mortality[ 11 - 13 ]. Regarding pulmonary and cardiac complications, however, results are conflicting.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, in patients ≥ 75 years, the nutritional status is often impaired [27] and the sarcopenia rate is higher [28,29]. However, none of the prospective cohort studies comparing younger (< 75 years) and older (≥ 75) cohorts found an association between age and postoperative morbidity or mortality [27,30].…”
Section: Patient Selection and Preparationmentioning
confidence: 99%